Does e-shopping replace shopping trips? Empirical evidence from Chengdu, China - Shi, Kunbo; De Vos, Jonas; Yang, Yongchun; Witlox, Frank (Transportation research. Part A, Policy and practice, 2019)
•E-shopping has a substitution effect on shopping trips.•Location plays an important role in e-shopping behavior.•The special context of China is a key determinant of e-shopping.•In the long run, the number of physical stores will decrease.•E-shopping could be a possible solution for urban congestion. With the rapid proliferation of e-retailing, the question of how e-shopping affects shopping travel has attracted increasing attention since the beginning of this century. To date, however, scholars have failed to reach a consensus on this topic. Meanwhile, China, where currently the highest level of e-retail shopping in the world takes place, has not received the full focus of previous studies. Using data from structured interviews with 710 respondents in Chengdu, China, we aim to explore whether e-shopping for four types of goods (clothes and shoes, electronics, food and drink, and cosmetics) replaces shopping trips. In addition, regression models are constructed to demonstrate the determinants of e-shopping and shopping travel behaviors. The results suggest that consumers’ e-shopping and shopping travel behaviors are significantly determined by sociodemographics, internet experience, car ownership, and location factors. E-shopping has a substitution effect on the frequency of shopping trips. It is further suggested that e-shopping could be regarded as a possible solution for urban congestion. In the long run, the number of physical stores for the four types of goods may decrease.